Membrane Electrode Assembly Based on Sulfonated Polysulfone-Activated Zeolite Composite Membrane for Fuel Cell Applications - Sri Mulijani; Yoki Yulizar; Armi Wulanawati (Jurnal Kimia Sains dan Aplikasi, 2026)
The depletion of fuel cell reserves shows the need for alternative energy sources. In this context, fuel cells provide a promising solution, generating power without emissions. The membrane electrode assembly (MEA) in fuel cells is a critical component to maximize combustion efficiency. Therefore, this study aims to develop MEA using a composite membrane based on sulfonated polysulfone-activated zeolite (PSfs-Z). The membrane was obtained by first sulfonating polysulfone (PSf) and then adding activated zeolite. Optimum fuel performance was achieved with the activated zeolite using 3 N HCl. Sulfonation was completed, as demonstrated by a sulfonation degree of 32.63%. The absorption bands of the SO2 group vibration from SO3H of PSfs were identified at a wave number of 1111.00 and 1259.33 cm−1. The successful formation of MEA was confirmed by its morphology, as observed using a scanning electron microscope, with the formation of a catalyst layer and a membrane in the cross-section. The highest proton conductivity and cell potential obtained for PSfs-Z 3 N MEA were 0.01727 S.cm−1 and 330 mV, respectively. This means the membrane electrode assembly based on a sulfonated polysulfone-activated zeolite composite membrane has a higher potential than the